(untitled) (Eurasian Journal of Philology Science and Education, 2016)
This article presents the etymology of the word «rating» and provides data on the scope of its use in the corpora of English and Russian languages. COHA (Corpus of Historical American English) is one of large corpora of the English language which gives us interesting tables and comparisons of «rating» over the years. We received the same facts about the Russian language from the national corpus of the Russian language. Based on such sources, synonymic series of the English word «rating» have been identified: score, grade, evaluation, ranking, sailor, mark, assessment. In the process of work with dictionaries it became clear that «rating» in Russian has such synonyms as оценка, популярность, чарт, порядок, показатель. The article gives the frequency of their use over the years. The corpora data enabled us to define phrases and to get some interesting semantics.